The origin and development of the CCAP in Zambia 1882-2004 - Coertzen, P; Chilenje, V (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
For a very long period of time the Church of Central Africa Presbyterian (CCAP) in Zambia had no record of its historical roots. As a result many Zambians questioned the independent existence of this church; others called it a “Malawian” church and others a “break away”. My hypothesis shows that it is clear from history that the CCAP existed among the Zambian people since the 1880’s. In addition it reveals that the CCAP in Zambia traces its roots from the Livingstonia Mission of the Free Church of Scotland which started its work in Central Africa in 1875 (Laws, 1934:7,16). Through this mission the church is known to have grown to a fully fledged denomination. It is also to be noted that the CCAP in Zambia is also a fruit of the activities of CCAP General Synod members in the urban areas.